2015
DOI: 10.1111/1468-4446.12163
|View full text |Cite
|
Sign up to set email alerts
|

Restabilizing attachment to cultural objects. Aesthetics, emotions and biography

Abstract: The scholarship on aesthetics and materiality has studied how objects help shape identity, social action and subjectivity. Objects, as 'equipment[s] for living' (Luhmann 2000), become the 'obligatory passage points humans have to contend with in order to pursue their projects (Latour 1991). They provide patterns to which bodies can unconsciously latch onto, or help human agents work towards particular states of being (DeNora 2000, 2003). Objects are central in the long term process of taste construction, as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This longstanding challenge to sociologists of art resonates with broader research suggesting cultural sociologists would benefit considerably from increased attention to materiality (Domínguez Rubio 2014;Griswold et al 2013;McDonnell 2010;Mukerji 1994), defined as how objects and environments act upon people to influence action in ways that cannot be reduced to cognitive representations (Mukerji 1997). See Benzecry (2015) for a helpful recent parsing of literatures on aesthetics and materiality. 5 My use of 'sensory conventions' draws on economic theories of conventions as shared templates for interpreting situations and structuring action (Biggart and Beamish 2003), but also on cultural and organizational studies of conventions in sociology, particularly Becker's ([1982] 2008) notion of art as the product of collective action and his view of culture as negotiated through interactions organized by conventions.…”
Section: Discussion and Conclusion: On The Implications Of Aesthetic mentioning
confidence: 99%
“…This longstanding challenge to sociologists of art resonates with broader research suggesting cultural sociologists would benefit considerably from increased attention to materiality (Domínguez Rubio 2014;Griswold et al 2013;McDonnell 2010;Mukerji 1994), defined as how objects and environments act upon people to influence action in ways that cannot be reduced to cognitive representations (Mukerji 1997). See Benzecry (2015) for a helpful recent parsing of literatures on aesthetics and materiality. 5 My use of 'sensory conventions' draws on economic theories of conventions as shared templates for interpreting situations and structuring action (Biggart and Beamish 2003), but also on cultural and organizational studies of conventions in sociology, particularly Becker's ([1982] 2008) notion of art as the product of collective action and his view of culture as negotiated through interactions organized by conventions.…”
Section: Discussion and Conclusion: On The Implications Of Aesthetic mentioning
confidence: 99%
“…For field theory, organizations, people, and goods use their symbolic and economic capital to reach or maintain an advantageous position in a given cultural field. Usage of such capital makes entry easier for conforming followers and more difficult for innovative newcomers (Allen and Lincoln 2004;Benzecry 2015;Foster et al 2011;Griswold et al 2013;Ravasi et al 2011). Unlike field theory, neo-institutionalist theory shows that the production and reception of influential cultural products is not exclusively driven by competition and power struggles among organizations or people in the cultural sector, and it highlights the role of knowledge experts in shaping key decisions within organizations (DiMaggio 1987;Franssen and Kuipers 2013).…”
Section: Literature Review and Theorymentioning
confidence: 99%
“…More recently one of the authors of this chapter (Benzecry, 2015) re-appropriated the Lacanian concept of partial object, or object a, in order to explain how amateurs who have been attached to a cultural object for a long time aim to find another object that would produce a similar emotional resonance. He used the idea of partial object in order to explain how amateurs engaged with a simile that lashed-up including some (but not all) of the artifacts, practices and technologies of the self glued together by the "original" cultural object.…”
Section: What Happens When the Other Is An Object?mentioning
confidence: 99%
“…Another line of research exploring how objects shape the nature of the social bond can be found in the renewed attention to the role that infrastructures and the built environment play in creating the silent linkages between action, choices and forms of judgment (Domínguez Rubio and Fogué, 2015). Some scholars have explored how urban planning and architecture have been used to hardwire moral and cultural categories into the built environment (Graham & MacFarlane, 2001, 2015Joyce 2003). Others have explored how the role of the built environment in the articulation different forms of participation and exclusion in the body politic (Lezaun & Marres, 2011), while others have focused on how contemporary processes of meaning-making or truth-making are mediated by the particular affordances offered by different media infrastructures and platforms (Parks and Starosielski, 2015;Gillespie, Boczkowski & Foot, 2014).…”
Section: What Are Objects Good For?mentioning
confidence: 99%